An Immunohistochemical Study of Cocaine- and Amphetamine-Regulated Transcript (Cart) Expression in the Pterygopalatine Ganglion of the Pig - Zacharko-Siembida Anna (Sciendo, 2017)
Although, a great effort has been made to understand the synthesis, regulation, processing and function of cocaine- and amphetamine-regulated transcript (CART) peptide at the central level, its peripheral function(s) are still obscure. Moreover, scarce studies describing the presence of CART in peripheral autonomic ganglia are mainly limited to laboratory rodents. Thus, the aim of the present study was to immunohistochemically investigate the expression of CART in Hu C/D-positive neurons of the porcine pterygopalatine ganglion (PPG). The distribution pattern of CART-IR nerve elements in PPG has been also assessed. The co-localization of CART with substance P (SP), galanin or somatostatin was studied by means of double immunohistochemical stainings. The presence of Hu C/D-positive/CART-positive neurons was detected both in the left and right PPG (4.7±1.2% and 5.2% ± 1.4%, respectively). The CARTimmunoreactive (IR) neurons were categorized as either middle (ca. 80%) or small (ca. 20%) in size. Moderate numbers of CART-IR boutons were also detected between CART-negative ganglionic neurons. CART-IR basket-like formations around PPG neurons were regularly observed. Virtually all CART-IR neurons additionally co-stored VIP, whereas none of the CART-expressing cells showed the presence of galanin, SP or somatostatin. CART-IR basket-like formations exclusively encircled VIP-IR PPG neurons. Thus, CART-IR nerve cells seem to constitute a relatively small homologous population of the porcine PPG neurons with largely unknown functions. Further functional studies aiming at whether CART-IR neurons could serve as interneurons are necessary.